Human capital investments in children: A comparative analysis of the role of parent-child shared time in selected countries - Eva Österbacka; Joachim Merz; Cathleen D. Zick (Leuphana Universität Lüneburg, Forschungsinstitut Freie Berufe (FFB), 2010)
Parents invest in their children's human capital in several ways. We investigate the extent to which the levels and composition of parent-child time varies across countries with different welfare regimes: Finland, Germany and the United States. We test the hypothesis of parentchild time as a form of human capital investment in children using a propensity score treatment effects approach that accounts for the possible endogenous nature of time use and human capital investment. Result: There is considerable evidence of welfare regime effects on parent-child shared time. Our results provide mixed support for the hypothesis that non-care related parent-child time is human capital enriching. The strongest support is found in the case of leisure time and eating time. – – Eltern investieren in ihre Kinder auf unterschiedliche Weise. Wir untersuchen wie das Ausmaß und die Zusammensetzung von Eltern-Kind Zeiten in unterschiedlichen Ländern mit differenten Wohlfahrtsregimes variiert: Finnland, Deutschland und die Vereinigten Staaten von Amerika. Komposition: Wir testen die Hypothese der Eltern-Kind Zeiten als eine Form von Humankapitalinvestitionen in Kinder mit einem 'propensity score treatment effects'-Ansatz für die mögliche Endogenität der Zeitverwendung und Humankapitalinvestition. Resultat: Wohlfahrtsregime haben einen signifikanten Einfluss auf die von Eltern mit ihren Kindern verbrachte Zeit. Unsere Resultate unterstützen die Hypothese, dass Eltern-Kind Zeiten, die nicht als Kinderbetreuung zu charakterisieren sind, Humankapital anreichern. Die stärkste Unterstützung wurde für die Bereiche Freizeit und gemeinsam verbrachte Essenszeiten gefunden.
Keywords: D1; J24; J22; H43; 330; parent-child time; comparative research; welfare regimes; Finland; Germany; USA; treatment effects; propensity score matching; Eltern-Kind Zeit; ländervergleichende Forschung parent-child time; comparative research; Wohlfahrtsregime; Finnland; Deutschland; Vereinigte Staaten von Amerika; Treatment effects; Propensity score matching; Kinderbetreuung; Eltern; Zeitverwendung; Bildungsinvestition; Kinder; Sozialstaat; Vergleich; Finnland; Deutschland; USA